ON THE QUESTION OF OBTAINING CEMENT FROM WESTERN UKRAINIAN RAW MATERIALS - DOROGAN, NATALIIA; CHERNYAK, LEV; SHNYRUK, OLEG (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Cement production is characterized by the consumption of large volumes of raw materials, the selection criteria for which are determined by their composition, reserves, and the ability to ensure stable supply to the plants. In this context, optimizing logistics emphasizes the relevance of using raw materials from sources located close to the manufacturing plant within the same region. This paper investigates the possibility of producing low-temperature-fired cement (≤1200 °C) with the integrated use of natural and technogenic raw materials from Western Ukraine, based on the limestone–perlite–fly ash system. The study employed a comprehensive approach, combining physico-chemical analysis methods for silicates and standardized technological tests of the binder material’s properties. The compositions of the raw material mixtures were calculated using the “RomanCem” computer program. The chemical–mineralogical features of limestone (as a carbonate-bearing component) and perlite and fly ash (as alumina- and silica-bearing components) were analyzed. Calculations of the quantitative ratios of the studied raw materials in the mixtures for cement production were performed, with an assessment of their compliance with the recommended modular characteristics. Based on these calculations and analyses, the compositions of the initial raw material mixtures in the limestone–perlite–fly ash system were determined, varying the quantitative ratio of perlite to fly ash from 1.0:1.2 to 2.0:1.0. The phase composition characteristics of cement produced from the investigated silicate systems at a firing temperature of up to 1100 °C were demonstrated, as well as the possibility of adjusting the properties of the mineral binder material by varying the developed initial mixture compositions. It was concluded that the technical and economic efficiency of regional cement production can be improved through the integrated use of raw materials from